2019
DOI: 10.1186/s13028-019-0448-2
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of extruded intervertebral discs in dachshunds: a radiographic, computed tomographic and histopathological study of 25 cases

Abstract: Background Three Nordic countries have national breeding programs to reduce the frequency of intervertebral disc disease in dachshunds. The programs include a radiographic examination of the vertebral column and dachshunds with more than four calcified discs visible on radiographs (CDVR) are discouraged from use in breeding. However, disc extrusion is also diagnosed in dachshunds without CDVR. The utility of the breeding programs is therefore questioned. Results A prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
2
28
0
1
Order By: Relevance
“…Among the Dachshund surgical cases in this study, 9.4% had no radiographic evidence of disc calcification. These results are similar to previous retrospective studies in Dachshunds and Pekingese that found that 13% and 17% of cases with disc extrusions had no radiographic calcification [39,40], likely reflecting low sensitivity (0.3–0.6) compared to histopathological assessment, as well as limitations of calcification as the sole marker for “clinically” relevant pathology [41,42].…”
Section: Discussionsupporting
confidence: 89%
“…Among the Dachshund surgical cases in this study, 9.4% had no radiographic evidence of disc calcification. These results are similar to previous retrospective studies in Dachshunds and Pekingese that found that 13% and 17% of cases with disc extrusions had no radiographic calcification [39,40], likely reflecting low sensitivity (0.3–0.6) compared to histopathological assessment, as well as limitations of calcification as the sole marker for “clinically” relevant pathology [41,42].…”
Section: Discussionsupporting
confidence: 89%
“…The latter progressively degenerates and calcifies in the late stage of IVD degeneration (2,17). In dachshunds with acute disc herniation, histopathology reveals that the majority of extruded disc material is calcified, even in the absence of radiographically visible calcification (18). More recent histopathological studies propose a grading scheme for intervertebral disc degeneration based on an assortment of parameters.…”
Section: Basic Pathological Mechanisms Of Canine Intervertebral Disc Degenerationmentioning
confidence: 99%
“…Intervertebral disc degeneration itself is known to increase the risk for compressive intervertebral disc disease and therefore neurological deficits. 8,35,36 Further, a significant association between intervertebral disc extrusion and kyphosis has been described for French Bulldogs and Pugs. 9,23 So, despite the low number of the two discussed vertebral malformations (14/707) associated with neurological deficits in this study, our findings can be interpreted in agreement with recent literature.…”
Section: Discussionmentioning
confidence: 92%
“…Faller et al 21 described a higher prevalence of intervertebral disc degeneration in dogs with kyphoscoliosis. Intervertebral disc degeneration itself is known to increase the risk for compressive intervertebral disc disease and therefore neurological deficits 8,35,36 . Further, a significant association between intervertebral disc extrusion and kyphosis has been described for French Bulldogs and Pugs 9,23 .…”
Section: Discussionmentioning
confidence: 99%